To the Mathematical Theory of the Temkin Adsorption Model - Vigdorowitsch, Michael; Tsygankova, Liudmila E.; Bernatsky, Pavel N. (Journal of Applied Solution Chemistry and Modeling, 2020)
This study expands the mathematical theory of the Temkin adsorption model and demonstrates the way experimental data are to be additionally treated. A functional complement property of the Temkin isotherm has been studied as a particular case of the common theory of asymptotic complement. This property is shown to give rise to various analytical strategies to be employed for processing or interpretation of the experimental results, e.g. to perform mapping of data obtained in experiments onto a conjugated part of the true isotherm, to judge if presupposed energetic heterogeneity type of the surface really takes place, etc. Experimental data for adsorption of carbon monoxide on gold and of sodium oleate on steel with and without a magnetite coating have been extensively analysed.